Evaluation of Drug Thiotriazoline in Patients with Alcoholic Hepatitis - A. V. Tkachev; T. A. Devlikamova; Z. H. Yandieva; A. S. Makarenko (Медицинский вестник Юга России, 2012)
Purpose: To evaluate the clinical efficacy and safety Thiotriazoline in patients with acute alcoholic hepatitis.Materials and Methods: The study included 67 patients with acute alcoholic hepatitis. Randomized patients were divided into two groups - primary and compared. Patients of the group (n = 35) received traditional treatment, in additionto which was connected hepatoprotector Thiotriazoline.Results: showed improvement of clinical, biochemical and instrumental parameterswhile taking the drug Thiotriazoline.Summary: The efficacy of treatment as measured by a combined index of overall effectiveness, the drug is comparable to that tiotreazolin with basic therapy, including the traditionally used hepatoprotectors.